Implementasi Algoritma Elias Gamma Code Untuk Kompresi File Video Pada Aplikasi Drama Korea - Dewi, Siagian (Jurnal Sains dan Teknologi Informasi, 2022)
Korean drama application is an application that is useful as a means of entertainment. When the user downloads the Korean drama application video on a smartphone (cellphone) and saves the video file downloaded by the Korean drama, it will produce a large file size. Because in general we do the activity of downloading many Korean drama videos, we get a long video duration. The longer the video duration, the larger the file size will be. Then the large file size will cause problems because it is limited by storage capacity. When you want to send it, it will take a long time to solve this problem, a solution is obtained by compression. The Elias Gamma Code algorithm is a lossless compression technique, which does not remove previous information, where the decompression results of the compressed video are the same as the original video file. By using the Elias Gamma Code algorithm, the Compression Ratio performance is 36%. These results prove that the compression of the downloaded video files by applying the Elias Gamma Code algorithm can reduce the size of large video files to be smaller than the original size.